Study guides

☆☆

Q: How do you solve x2 plus 7x plus 12?

Write your answer...

Submit

Related questions

x2+7x+12=0 x2+7x=-12 x+Sqaure Root of 7x= 2(SQ Root Symbol)3

=3x * * * * * The correct answer is: x2 + 7x + 12 = (x + 3)(x + 4).

x2-7x+12 (x-3)(x-4)

Do you mean x2+7x+12? If so then it is: (x+3)(x+4)

x^2 +7x+12 = (x+3)(x+4) when factored

x2 + 7x = 2x2 + 6 x2 - 2x2 + 7x = 6 -x2 +7x - 6 = 0 or alternatively x2 - 7x + 6 = 0

X2+11x+11 = 7x+9 X2+11x-7x+11-9 = 0 x2+4x+2 = 0 Solve as a quadratic equation by using the quadratic equation formula or by completing the square: x = -2 + or - the square root of 2

x=4 x=0

x2 + 7x + 6 = (x + 6) (x + 1)

It is (x+3)(x+4) when factored

The value of x2+7x+10 depends on the value of X. If x=1, then x2+7x+10 = 18 If x=2, then x2+7x+10 = 28 If x=3, then x2+7x+10 = 40 and so forth

x2 + 7x - 8 = (x + 8)(x - 1)

x2+7x-8 = (x-1(x+8)

-x2+7x+18 = (-x-2)(x-9) when factored

x2-7x+12 = 0 (x-3)(x-4) = 0x=3,4

(x + 3)(x + 4)

It is (x-3)(x-4) when factored

x2 + 7x + 10 = (x + 2)(x + 5)

i got 42 divided 7x

x2 + 7x = 0 => x*(x + 7) = 0 => x = 0 or x + 7 = 0 so that x = 0 or x = -7

x2 + 7x + 9 = 3 ∴ x2 + 7x + 6 = 0 ∴ (x + 6)(x + 1) = 0 ∴ x ∈ {-6, -1}

x2+7x+12=0usually this means to factor the equation.factored this equation would be...(x+3)(x+4)

1

(x-3)(x-4)

x2 - 7x = 60 x2 - 7x - 60 = 0 (x - 12) (x + 5) = 0 x = 12 or x = -5